Studies on phytochemical and antibacterial activity of methanol, ethanol and acetone extracts of Grewia orientalis leaves - Totakura Naga Prathyusha; Vupputuri Panchakshari; Medaboina Guravaiah; Neelam Sridevi; chandra bala sekaran (International Journal of Phytomedicine, 2013)
Three solvent extracts (methanol, ethanol and acetone) of Grewia orientalis leaves were screened for potential antibacterial activity against Escherichia coli, Bacillus substilis, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumoniae and Bacillus thuringienis. The agar disk diffusion method using filter paper disks was used to study the antibacterial activity of Grewia orientalis leaf extracts against 6 microbial strains. All the three extracts did not exert any inhibitory action on Bacillus thuringienis. The highest antibacterial potentials were observed for the acetone extract, followed by methanol and ethanol extracts. The Minimum Inhibitory Concentration (MIC) of the plant extracts were ranging from 50 to 250 μg/ml. The preliminary phytochemical screening of extracts was carried out for major phytochemical derivatives in Grewia orientalis.